Respostas

2013-12-13T14:14:07-02:00
METODO DA COMPARACAO                      METODO DA SUBSTITUICAO
  y = 2 x                                                            2 x - y = 3               2 x = 3 + y
y + 5 x = 14                                                      3 x + 2 y = 8               x = 3 + y / 2                                                              
          3 ( 3 + y /2 ) + 2 y = 8
2 x + 5 x = 14                                                    9 + 3 y / 2  + 2 y = 8
 7 x = 14                                                           9 + 3 y + 4 y = 16
 x = 14 : 7                                                           7 y = 16 - 9
 x = 2                                                                   7 y = 7
y = 2 . 2      y = 4                                                   y = 7 : 7      y = 1
 S = { 2 , 4 }                                                           x = 3 + 1 / 2
                                                                             x = 4 : 2     x = 2
                                                                            S = { 2 , 1 }

                                                                            

1 5 1